Fabrication of Chrysin-Loaded Hyaluronic Acid Decorated Niosomal Nanoparticles: Potential Anti-inflammatory and Anti-osteoclastic Effects on PBMCs of Rheumatoid Arthritis Patients - Sarah Nadhim Sahib; Fadhil Jawad Al-Tu’ma; Atheer Hameed Odda; Maha M. Kadhim Al-Tu’ma (Advanced Pharmaceutical Bulletin)
Purpose: Rheumatoid arthritis is a persistent autoimmune condition characterized by joint inflammation and degradation, impacting individuals with varying degrees of severity. Chrysin is a natural flavonoid possessing diverse pharmacological properties and antioxidant and anti-inflammation activities. However, chrysin encounters limitations in bioavailability due to its low aqueous solubility and rapid metabolism. Targeted therapy using nanoparticle systems is a novel approach to overcome these difficulties. Methods: The hyaluronic acid-decorated niosomal nanoparticles (NPs) were fabricated using the thin-film hydration method and characterized by various techniques (DLS, AFM, SEM, FT-IR, and drug release pattern analysis). The peripheral blood mononuclear cells (PBMCs) were isolated from blood samples of patients with rheumatoid arthritis, and various factors levels, including nitric oxide, tumor necrosis factor alpha (TNF-α), interleukin (IL)-1β, IL-10, total antioxidative capacity (TAC), superoxide dismutase (SOD), glutathione peroxidase (GPx), as well as the expression levels of TIMP1, MMP9, and RANKL genes were evaluated. Results: The fabricated NPs demonstrated spherical morphology with 199±10.7 nm size, 0.653 PDI, and −15.38±2.8 zeta potential. The FT-IR results confirmed the successful incorporation of substances inside niosomal NPs. The treatment with chrysin loaded niosomal NPs successfully decreased the inflammatory agent (nitric oxide), inflammatory cytokines (IL-1β and TNF-α), and osteoclastic related genes (MMP9 and RANKL) expression level. On the other hand, the activity of antioxidant agents (TAC, SOD, and GPx), anti-inflammatory cytokine (IL-10), and anti-osteoclastic related genes (TIMP1) were found to increase. Conclusion: Taken together, the hyaluronic acid-decorated niosomal nano drug delivery system was acceptable in terms of characteristics and was able to direct the chrysin in the vicinity of PBMCs.